Hedges Used In Twilight Novel " New Moon " Writen ByStephenie Meyer: A Sociolinguistics Perspective - Primaresty, Fera Julia Mega, Drs. Maryadi M. A., Mauly Halwat Hikmat, Ph. D (2014)
This research aims at describing the types of hedges which are used in Twilight novel "New Moon" written by Stephenie Meyer, and its motives of using hedges. The type of research is descriptive qualitative. The writer focuses on analyzing the types of hedges, that is used in Twilight novel "New Moon" written by Stephenie Meyer. The hedges as the object of the data. The data taken are words, phrases, clauses, and sentences which contain hedges. The source of data are taken from "New Moon" novel written by Stephenie Meyer. The method of collecting data is documentation and the step are reading, watching, signing, and coding the data. The analysis of the motives, the writer uses sociolinguistics analysis especially in hedges theory which is used by Lakoff (1973). The result of the research show that firstly: there are 10 kinds of hedges which are used in women's speech namely: (1) Lexical hedges or fillers (37,5%), (2) Tag questions (12,5%), (3) Rising intonation (1,78%), (4) Intensifiers (33,9%) (5) Avoidance of strong swear words (7,1%), (6) Emphatic stress (7,1%). The hedges used are fillers ( 37,5%), intensifiers (33,9%), tag questions (12,5%), avoidance of strong swear words (7,1%), emphatic stress (7,1%), and rising intonation (1,7%). The mostly motives which are used by people are makes sentence fuzzier (21,4%), to assure the hearer (14,2%), to ask confirmation (14,2%), to appreciate something (7,1%),to interrupt (5,3%), to make sentence more fun (3,5%), and to fathic communion (1,7%).